Seed Germination and Seedling Growth of Dendrocalumus brandisii in vitro, and the Inhibitory Mechanism of Colchicine - Lv, Zhuo; Zhu, Fangwei; Jin, Diankun; Wu, Yufang; Wang, Shuguang (Frontiers in Plant Science, 2021)
Bamboos seldom bloom and almost no seeds could be harvested, and, hence, few works are focused on germination physiology. Systematic research on the physiological effects of colchicine on germination and seedling growth of bamboo seeds is lacking. In this study, we finely recorded seed germination and seedling growth of Dendrocalamus brandisii in media supplemented with different colchicine concentrations. Physiological effects and mechanisms of colchicine were analyzed. The results showed that D. brandisii seeds were non-dormant, and seed lots achieved their highest germination rates on the 4th day and finished the whole germination period after 21 days. Colchicine inhibited seed germination and seedling growth but did not change its germination pattern. Seed germination and seedling growth decreased constantly with colchicine concentration. Colchicine showed more negative effects on seedling growth than on seed germination and root growth. High concentrations of colchicine retarded the development of plumules and even caused their aberrant development. Under tissue culture conditions, seed germination, and seedling growth relied mainly on the endogenous starch and soluble sugar degradation, in which α-amylase, STP, and SUSY played the key role. Colchicine inhibited seed germination and seedling growth by suppressing the α-amylase, STP, and SUSY activities. Colchicine showed more negative effects on sucrose degradation than on starch degradation during seed germination and seedling growth. This study provides new basic information on the seedling physiology for the genetic breeding of bamboo plants.